Preparation, structure and application of styrene-acrylic emulsion/modified ammonium polyphosphate in flame retardant air filter paper. Issue 4 (June 2022) - Jun, Yan; Jin, Yang; Lele, Sun; Guilong, Xu; Zhaohui, Li
The filter paper of automobile engine air filter is easy to temper and causes combustion. Flame retardant is usually added to the reinforced resin styrene-acrylic emulsion (SAE) to improve the flame-retardant performance of the air filter paper. Ammonium polyphosphate (APP) was used as material in this research, and multi-layer coated APP was prepared by microcapsule coating. A layer of nano-scale SiO2 was coated and then introduced organosiloxane structure of the allyl polyoxypropylene ether side chain and boron. The chemical groups and structural composition were determined by Fourier transform infrared spectroscopy. TGA characterized the modified particles' high-temperature stability. By scanning electron microscopy and TEM, the morphologies of modified particles were analyzed to reveal the evolution of modified APP in SAE. Finally, nanoparticles with core-shell structures were formed. Applying the blended resin to the air filter paper, the flame-retardant performance was greatly improved. Total heat release (THR), heat release rate (HRR), peak heat release rate (pkHRR), mass loss rate (MLR), and effective heat of combustion (EHC) were reduced, respectively, by 30.8%, 30.7%, 42.0%, 16.7%, and 14.4%. The time to ignition (TTI) was doubled, so the fire spread could be effectively suppressed. Meanwhile, nano latex particles were attached to the interwoven fibers points and formed a "sea-island structure, " which significantly improved the paper's mechanical properties, with bursting strength, tensile strength, stiffness, fracture work, and elongation increased by 18.60%, 5.72%, 10.64%, 17.00%, and 81.80%, respectively. It solved the problem that the inorganic flame-retardant particles often lead to the deterioration of the mechanical properties of paper.